The Wishing Box e The Fifty-Ninth Bear: a rasura do casamento em Sylvia Plath - Oliveira, Matheus Torres de (2018)
The present thesis aims to study the short stories The Wishing Box and The Fifty-Ninth Bear, by Sylvia Plath, under theoretical and critical perspectives which allow it to observe a dialogue in those texts with their historical context, on a dialectical relation between form and content as postulated by Fredric Jameson. We intend to elucidate how those narratives can be read beyond the autobiographical and therefore they articulate in their formal structure a female critical view of marriage in Cold War America. Historicizing both of these short stories using alterity as mediator and following the cultural model of understanding the female literary tradition, we will semantically broaden her criticism by inserting the fragments in the History. In addition, this critical exam, by electing Plath's short prose, allows us to shed light on the overlooked scope of her ouvre.